Creative women in Ireland : not your muse - O'Driscoll, Aileen (New York, NY : Routledge, 2023)
"Through the contributions of women working in the creative industries, this timely book explores the role of creativity in their lives, the experiences that have positively contributed to and supported their creativity and their work, as well as how gendered considerations intersect with their involvement in the cultural sphere. Spanning psychology, cultural and media studies, and the philosophy of art, it builds on existing research by offering examples of the abundance of creativity residing in women working in film and television, architecture, design, music, theatre, and the performing and visual arts in Ireland. Their reflections offer a valuable counter perspective to the assumption that women are more naturally the 'muse' than the creator. From these conversations, some common, although at times diverging, experiences in childhood, early career and approaches to their creative work offer important insights into the nature and practice of creativity and the conditions that may best nurture and support creativity in girls and women. Providing original observations into gendered understandings of creativity, this book will be essential reading for researchers, advanced students and practitioners seeking contemporary insights on creativity, feminism and gender"--
OCLC-licensed vendor bibliographic record.
Keywords: Creative ability in women -- Ireland; Cultural industries -- Ireland; Women -- Psychology; BUSINESS & ECONOMICS / Museum Administration & Museology; BUSINESS & ECONOMICS / Nonprofit Organizations & Charities; ART / Business Aspects